Проблеми визначення предмета доказування у справах про визнання необґрунтованими активів та їх стягнення в дохід держави - Кройтор, В. А.; Kroytor, V. A. (Науковий вісник Міжнародного гуманітарного університету. Сер.: Юриспруденція. - 2023. - № 63. - С. 92-96, 2023)
Досліджено актуальне питання визначення предмета доказування в справах про визнання необґрунтованими активів та їх стягнення в дохід держави. Доведено, що позиція вчених, які розуміють предмет доказування в широкому значенні, є спірною. Наголошено, що в цивільному судочинстві слід виділяти загальний предмет доказування по конкретній категорії цивільних справ і конкретний предмет доказування залежно від обставин певної цивільної справи. А вже встановлення конкретного предмета доказування залежить від обставин певної цивільної справи, яка розглядається та вирішується в суді.

The scientific article is focused on studying the topical issue of determining the fact in proof in cases of recognizing inconsistent assets and their collection into government revenue. The author of the article has proved that the point of view of scholars who understand the fact in proof in a broad sense is controversial. It is wrong to single out the facts in proof for the participants in the case or to include all the circumstances (facts) that are established in one way or another during civil case proceedings into the fact in proof. Currently. The author of the paper supports the point of view of scholars (Ya.M. Sadykova and others) regarding the possibility of distinguishing the definition of the general fact in proof within a specific category of civil cases and the specific fact in proof depending on the circumstances of a certain civil case. Analysis of the Articles 290–292 of the Civil Procedural Code of Ukraine allows to make a conclusion about the possibility of distinguishing the following general fact in proof in cases of recognizing inconsistent assets and their collection into government revenue: 1) assets acquired after the date of entry into force of the Law of Ukraine “On Amending Certain Legislative Acts of Ukraine Regarding the Confiscation of Illegal Assets of Persons Authorized to Perform the Functions of the State or Local Self-Government and Punishment for the Acquisition of Such Assets”; 2) assets acquired by a person authorized to perform the functions of the state or local self-government (the list of such persons is specified in paragraph 1, Part 1 of the Art. 3 of the Law of Ukraine “On Prevention of Corruption”) and/or another individual or legal entity who acquired such assets on behalf of a person authorized to perform the functions of the state or local self-government, or if the person authorized to perform the functions of the state or local self-government can directly or indirectly perform actions with respect to such assets that are identical in content to exercising the right to dispose them; 3) acquisition of assets on a legal basis; 4) the difference between the value of such assets and the legal income of a person authorized to perform the functions of the state or local self-government is five hundred or more times greater than the subsistence minimum for able-bodied persons, established by law on the date of entry into force of the mentioned Law. The author of the paper has concluded that the specific fact in proof depends on the circumstances of a certain civil case.

Исследован актуальный вопрос определения предмета доказывания по делам о признании необоснованными активов и их взыскании в доход государства. Доказано, что позиция ученых, понимающих предмет доказывания в широком смысле, спорна. Отмечено, что в гражданском судопроизводстве следует выделять общий предмет доказывания по конкретной категории гражданских дел и предмет доказывания в зависимости от обстоятельств определенного гражданского дела. А установление конкретного предмета доказывания зависит от обстоятельств определенного гражданского дела, которое рассматривается и решается в суде.
Problems of determining the fact in proof in cases of recognizing inconsistent assets and their collection into government revenue
Keywords: цивільне судочинство; civil justice; гражданское судопроизводство; докази; evidence; доказательства; доказування; proving; доказывание; предмет доказування; subject of proof; предмет доказывания; необгрунтовані активи; unsubstantiated assets; необоснованные активы; справи про визнання необґрунтованими активів та їх стягнення в дохід держави; cases on recognition of assets as unsubstantiated and their collection into state income; дела о признании необоснованными активов и их взыскании в доход государства